Analisis Kestabilan Tunnel Berdasarkan Klasifikasi Geomekanika (RMR-System) Pada Penambangan Batubara Bawah Tanah Metoda Room and Pillar PT. Allied Indo Coal Jaya (AICJ) Sawahlunto - Muhammad Deno Akbar; Bambang Heriyadi; Ansosry Ansosry (Departemen Teknik Pertambangan FT UNP, 2019)
Abstract. Excavation of tunnels in underground mines is quite a complex job, because it will give a change in balance from rock conditions that can be failure. This research was conducted to determine rock strength, rock mass class, and open hole stability based on the potential of wedge debris by estimating the Safety Factor (FS) value of the planned tunnel. Based on the RMR-System method, the value for coal is 49 points, where this rock is included in class III (fair rock) with maximum stand up time is 310 hours (±13 days) for 3m of span. The results of the RMR ground support recommends using Rock bolt with a diameter of 20 mm, fully grounted length 4 m, and spacing 1.5-2 m. Another alternative is to use a Class V wooden stand. Based on the results, the value of safety factor (FS) on the roof (siltstone) is 1,944, FS on the left wall (Coal) is 1,346, and the right wall (Coal) is 4,067. From the results of rock reinforcement using the RMR-System ground support recommendations, the result is an increase in the Safety Factor (FS) value from the value of 1,346 to 2,377 so that the wedge is more stable.Keywords: Tunnel, Safety Factor (FS), RMR System , Stand-Up Time, Ground Support.